Peningkatan Produktivitas BumDesa Melalui Pendampingan Perijinan dan pemasaran Produk UMKM Unggulan Desa Pecatu, Bali - Sasadara, Maria Malida; Yuda, Putu Era Sandhi Kusuma; Cahyaningsih, Erna; Dewi, Ni Luh Kade Arman Anita; Tirtayasa, Gede Agus Ari (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2026)
UMKM Boga Sari Pecatu is a community-based small enterprise fostered by BUMDesa Catu Kwero Sedana Pecatu, specializing in the production of herbal goods. To enhance the productivity of the BUMDesa, the village has designated several flagship products for wider market development, including instant ginger powder to be produced by UMKM Boga Sari Pecatu. Although the UMKM has produced several items, it faces key challenges such as the absence of production permits, limited production facilities that hinder scale‐up, the lack of product branding, and the absence of standardized bookkeeping practices. Through this community service initiative, the implementing team carried out several programs to address these issues, including assistance in fulfilling PIRT registration requirements, procurement of a ginger grater machine to support larger‐scale instant ginger powder production, development of a UMKM logo along with packaging design and labelling, and training on simple bookkeeping practices applicable to small enterprises. The program, conducted by the Faculty of Pharmacy, Universitas Mahasaraswati Denpasar, proceeded smoothly and according to plan. The major focuses included permit facilitation, provision of production equipment, and strengthening of product branding through the development of logos and packaging labels. The outcomes indicate improved partner understanding of PIRT procedures and benefits, although the permit issuance process is still ongoing. In terms of branding, the UMKM now possesses a new logo and compliant packaging label design, enhancing product readiness for broader distribution. Bookkeeping training likewise improved partner knowledge, as reflected in the differences between pre-test and post-test scores